World Academy of Science, Engineering and Technology - Rohasliney, Hashim (Pusat Pengajian Sains Perubatan, 2010)
Abstract-A phenomenological model for spedcs spreading which incorporates the Allee effect, a species' maximum attainable growth rate, co!lective dispersal rate and dispersal adaptability is presented. This builds on a well-established reaction-diffusion model for spatial spreading of invading organisms. The model is phrased in tenns of the "hostility" (which quantifies the Allee threshold in relation to environmental sustainability) and dispersal adaptability (wbich measures how a spe<:ies is able to adapt its migratory response to environmental conditions). The species' invadingln:tteating speed and the shatpness of the invading boundary are explicitly characterised in terms of the fundamental parameters, and analysed in detail.